2020
DOI: 10.1002/cssc.201903438
|View full text |Cite
|
Sign up to set email alerts
|

Plasma‐Driven in Situ Production of Hydrogen Peroxide for Biocatalysis

Abstract: Supporting Information and the ORCID identification number(s) for the author(s) of this article can be found under: https://doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 65 publications
0
34
0
1
Order By: Relevance
“…[3] One approach makes use of atmospheric pressure plasmas. [4] In general, plasmas are generated by high electric fields, accelerating free electrons that collide with atoms or molecules in the gas phase, which leads to the formation of metastable as well as excited species and ions. [5] The shortliving reactive species react with each other or with surrounding gas atoms or molecules to eventually yield less reactive species.…”
Section: Main Textmentioning
confidence: 99%
See 2 more Smart Citations
“…[3] One approach makes use of atmospheric pressure plasmas. [4] In general, plasmas are generated by high electric fields, accelerating free electrons that collide with atoms or molecules in the gas phase, which leads to the formation of metastable as well as excited species and ions. [5] The shortliving reactive species react with each other or with surrounding gas atoms or molecules to eventually yield less reactive species.…”
Section: Main Textmentioning
confidence: 99%
“…We previously showed that the H 2 O 2 in plasma-treated buffers can drive biocatalysis with the in vitro-evolved, recombinant UPO from Agrocybe aegerita (rAaeUPO). [4] When enzyme and substrate were treated together with plasma, however, the yield of product was significantly reduced as compared to a catalysis scheme in which plasma treatment and subsequent biocatalysis were uncoupled. Since the enzyme was quickly inactivated by plasma treatment with a dielectric barrier discharge (DBD), immobilization was used to prolong the lifetime of the enzyme.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…In agriculture, exposure to PAW can lead to enhanced seed germination and growth of plants [9] in addition to its strong bactericidal effect [10]. Further applications of discharge plasmas generated in liquids include chemical synthesis [11][12][13], nanoparticle synthesis [14][15][16], destruction of pollutants in wastewaters [17][18][19][20][21][22], polymer surface treatment [23][24][25], etc. Nevertheless, the main hindrance remains in place even after two decades of intensive research effort: What is an effective method for large-volume liquid treatment?…”
Section: Introductionmentioning
confidence: 99%
“…Introduction of the gas-phase allows reduction of breakdown strength to technically more feasible values of 10 kV/cm. Typical representatives of such an approach include plasma jets submerged in liquid [7,11,27]; discharges generated above [10,13] or from the liquid surface [25], discharges in liquid aerosol [3]; or discharges initiated inside the gas micro-bubbles introduced [21] or formed inside the liquid volume [18,24]. Still, none of these methods of discharge plasma generation can deliver a sufficiently high and cost-effective throughput of plasma-treated liquid (see Table 1).…”
Section: Introductionmentioning
confidence: 99%